2022
DOI: 10.1002/jmv.27867
|View full text |Cite
|
Sign up to set email alerts
|

SARS‐CoV‐2 Omicron BA.1 variant breakthrough infections in nursing home residents after an homologous third dose of the Comirnaty® COVID‐19 vaccine: Looking for correlates of protection

Abstract: We investigated whether peripheral blood levels of SARS-CoV-2 Spike (S) receptor binding domain antibodies (anti-RBD), neutralizing antibodies (NtAb) targeting Omicron S, and S-reactive-interferon (IFN)-γ-producing CD4 + and CD8 + T cells measured after a homologous booster dose (3D) with the

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
16
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 19 publications
(20 citation statements)
references
References 20 publications
1
16
0
Order By: Relevance
“…Among the recipients of the third-dose who had close contact with COVID-19 patients during the Omicron wave, we observed no measurable differences in the levels of live-virus Nab against Omicron variants and anti-spike antibodies between breakthrough infection cases and their controls. This result is consistent with the findings of a study of nursing home residents, which showed no difference in pseudo typed virus NAb titers against Omicron following the third vaccination between Omicron-infected patients and arbitrarily selected controls [9]. These results suggest that among healthy people, breakthrough infections with highly immune-evasive Omicron variants may occur independent of the humoral immune response to the third-dose vaccine.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…Among the recipients of the third-dose who had close contact with COVID-19 patients during the Omicron wave, we observed no measurable differences in the levels of live-virus Nab against Omicron variants and anti-spike antibodies between breakthrough infection cases and their controls. This result is consistent with the findings of a study of nursing home residents, which showed no difference in pseudo typed virus NAb titers against Omicron following the third vaccination between Omicron-infected patients and arbitrarily selected controls [9]. These results suggest that among healthy people, breakthrough infections with highly immune-evasive Omicron variants may occur independent of the humoral immune response to the third-dose vaccine.…”
Section: Discussionsupporting
confidence: 91%
“…Several studies have shown an inverse relationship between vaccine-induced antibody levels and infection risk, whereas others have suggested that infection occurs irrespective of the antibody levels. Data regarding the association between vaccine-induced immunogenicity and infection risk during the Omicron epidemic are limited [9], which has increased transmissibility and high immune evasion. VE studies have reported a higher ratio of asymptomatic patients to overall infected patients in vaccinated COVID-19 patients than in unvaccinated patients [10, 11], suggesting a suppressive role of the vaccine against symptoms of infection.…”
Section: Introductionmentioning
confidence: 99%
“…(32). This could indicate that neutralising titres against the Omicron variant may not reliably predict at the individual level the risk of SARS-CoV-2 infection (6, 23, 33), conversely to that described for previous VOCs (34). Nevertheless, we could not conclude as to the value of neutralising antibodies as a CoP for Omicron BA.1 variant in the present study as we selected a subset of patients with high anti-RBD IgG levels for the analysis of neutralising antibodies.…”
Section: Discussionmentioning
confidence: 89%
“…An effect similar to “Wild sera” (Figure 3C), was observed in “Vaccine sera” (Figure 4C), as all vaccines used globally are based on the Wuhan‐Hu‐1 spike. Delta and Omicron strains have been shown to evade vaccine‐induced immunity and cause breakthrough infections 13,29–32 . In Delta breakthrough, a preferential boosting of ancestral (Wuhan‐Hu‐1) and homologous (Delta) immunity was seen but not to successor (Omicron) variants.…”
Section: Discussionmentioning
confidence: 99%